2017
DOI: 10.4048/jbc.2017.20.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Breast Cancer: A Clinical Review and Update

Abstract: Sentinel lymph node biopsy has become a standard staging tool in the surgical management of breast cancer. The positive impact of sentinel lymph node biopsy on postoperative negative outcomes in breast cancer patients, without compromising the oncological outcomes, is its major advantage. It has evolved over the last few decades and has proven its utility beyond early breast cancer. Its applicability and efficacy in patients with clinically positive axilla who have had a complete clinical response after neoadj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 98 publications
(113 reference statements)
0
65
0
3
Order By: Relevance
“…For example, in the field of breast cancer, several studies have reported on the learning curve for axillary SLN mapping during the early days of adoption of SLN biopsy 11–15 . Following extensive investigation of its safety and efficacy, SLN biopsy has become a standard staging tool in the surgical management of breast cancer 16 . In contrast, only two published poster presentations have assessed the learning curve for SLN dissection for gynecologic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the field of breast cancer, several studies have reported on the learning curve for axillary SLN mapping during the early days of adoption of SLN biopsy 11–15 . Following extensive investigation of its safety and efficacy, SLN biopsy has become a standard staging tool in the surgical management of breast cancer 16 . In contrast, only two published poster presentations have assessed the learning curve for SLN dissection for gynecologic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] Following extensive investigation of its safety and efficacy, SLN biopsy has become a standard staging tool in the surgical management of breast cancer. 16 In contrast, only two published poster presentations have assessed the learning curve for SLN dissection for gynecologic cancer. Desai et al 17 used the CUSUM method to assess the learning curve in 120 patients with endometrial carcinoma who underwent robot-assisted laparoscopy.…”
Section: Comparisons Between the Cases From The Early Period And Thmentioning
confidence: 99%
“…Another promising method which might provide a more accurate identification of patients who present ovarian cancer lymph node metastases even in apparently early stages of the disease is represented by the sentinel node detection [4]. The method, which has been widely implemented in cases diagnosed with early stage breast cancer, melanoma and even gynecological cancers (such as endometrial cancer or cervical cancer), is still under evaluation in patients with presumed early stage ovarian cancer, further studies being still needed before introducing it as part of the standard therapeutic protocol [4,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the concept of sentinel lymph node detection has been proposed, initially in the Eastern countries, and later on, but with a lower enthusiasm, in the Western countries. The method, successfully implemented by Cabanas in penile cancer patients and by Morton in malignant melanoma patients, has become nowadays the standard of care in early stage breast cancer as well as in melanoma [7][8][9][10][11] . In breast cancer and malignant melanoma patients, the method presents a particular interest due to the fact that it can provide an efficient staging of the disease and an adequate tailoring of the adjuvant oncologic treatment [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%